Robust coordinated control using backstepping of flywheel energy storage system and DFIG for power smoothing in wind power plants - Mohamed Nadour; Ahmed Essadki; Tamou Nasser; Mohammed Fdaili (Institute of Advanced Engineering and Science, 2019)
This paper presents a robust coordinated control of a flywheel energy storage system (FESS) and a doubly fed induction generator (DFIG) based wind energy conversion system (WECS), used to smooth the wind induced output power fluctuations. The overall system control combines field oriented control schemes and nonlinear backstepping approach applied first, to the machine side converter (MSC) to regulate the DFIG active and reactive power in order to ensure maximum power point tracking (MPPT) operation and a unity power factor at the point of common coupling (PCC). Then, to the grid side converter (GSC) to maintain a constant DC bus voltage. Finally, to the flywheel side converter (FSC) in way that allows the storage unit to serve as a buffer that stores energy in the case of excess power and retrieves it back into the output in the case of power deficiency. A numerical simulation using Matlab/Simulink software validates the effectiveness of the proposed control strategies in terms of dynamic response, improvement of generated power quality and robustness against parametric variation.